Preparation method for manufacturing inorganic fiberboard by using liquid glue

Through plasma surface treatment and the use of nanoparticle additives, the binding force and mechanical properties of inorganic fiberboard are improved, and the problems of insufficient binding force and low production efficiency in traditional methods are solved, and the manufacturing of high-performance inorganic fiberboard is realized. It is suitable for more Wide range of application fields.

CN119141660AInactive Publication Date: 2024-12-17BUCKWIND IND (HUIZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411513189.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In traditional inorganic fiberboard manufacturing methods, the binding force between fiber and adhesive is insufficient, resulting in poor mechanical performance of the sheet, complex production process and high cost, which limits its application in high-end fields.

Method used

Plasma surface treatment technology is used to modify the inorganic fibers, and liquid adhesives containing modified polyurethane or modified epoxy resin are installed, nanoparticle additives are added, and efficient mixing is carried out at suitable temperatures through a high-speed disperser for molding and rapid formation. Thermal curing treatment and surface coating treatment is performed to enhance the performance of the sheet.

Benefits of technology

It significantly improves the bonding power between fiber and adhesive, improves the overall strength, durability and scratch resistance of the sheet, simplifies the production process, reduces costs, and expands the application field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119141660A_ABST
    Figure CN119141660A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fiberboard manufacturing, and discloses a method for manufacturing an inorganic fiberboard through liquid glue, which comprises the following steps: (a) carrying out surface modification on inorganic fibers by adopting a plasma surface treatment technology so as to enhance the binding force between the fibers and an adhesive; (b) preparing a liquid adhesive containing modified polyurethane or modified epoxy resin, wherein the liquid adhesive contains a nanoparticle additive; (c) efficiently mixing the inorganic fibers with the liquid adhesive through a high-speed disperser; (d) molding the mixed materials through molding equipment; the inorganic fibers are subjected to surface modification by adopting a plasma surface treatment technology, the interface bonding force between the fibers and the adhesive is remarkably improved, the bonding force between the fibers and the adhesive is enhanced by adding the nano particle additive into the liquid adhesive, and the bonding force between the fibers and the adhesive is improved. And the mechanical properties such as tensile strength, compressive strength and elastic modulus of the plate are also obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fiberboard manufacturing, in particular to a preparation method of inorganic fiberboard by using liquid glue. Background Art

[0002] As an important building material and industrial material, inorganic fiberboard is widely used in thermal insulation, fire prevention and sound insulation. The traditional method of manufacturing inorganic fiberboard usually uses dry powder adhesive mixed with inorganic fiber, and then hot press molding. This method has some disadvantages, such as weak bonding between fiber and adhesive, resulting in poor mechanical properties of the board, as well as complex production process and high cost.

[0003] The common inorganic fiberboard manufacturing methods on the market currently have the following problems:

[0004] Insufficient bonding strength: The bonding strength between fiber and adhesive in traditional methods is weak, which affects the overall strength and durability of the board.

[0005] Low production efficiency: The existing manufacturing process is relatively complex and the production cycle is long, which limits output and cost control.

[0006] Performance limitations: Existing inorganic fiberboards perform generally in terms of scratch resistance and chemical resistance, which limits their application in high-end fields. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing an inorganic fiberboard using a liquid glue to solve the problems raised in the above background technology.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] The method for preparing inorganic fiberboard by liquid glue comprises the following steps:

[0010] (a) Using plasma surface treatment technology to modify the surface of inorganic fibers to enhance the bonding force between the fibers and the adhesive;

[0011] (b) preparing a liquid adhesive comprising modified polyurethane or modified epoxy resin, wherein the liquid adhesive contains a nanoparticle additive for further enhancing the bonding force with the inorganic fiber;

[0012] (c) efficiently mixing the inorganic fiber with the liquid adhesive by a high-speed disperser at a temperature of 20° C. to 40° C.;

[0013] (d) forming the mixed material through a forming device, wherein the forming process includes pressurizing the mixed material to a pressure in the range of 5 MPa to 20 MPa through a hydraulic press;

[0014] (e) performing rapid thermal curing treatment on the formed sheet;

[0015] (f) performing post-processing, including precision cutting and fine grinding, and also including surface coating treatment, wherein the coating contains nano-scale fillers and functionalized polymers.

[0016] Preferably, the inorganic fiber is selected from one or more of glass fiber, rock wool fiber, ceramic fiber, and calcium silicate fiber, and the inorganic fiber is pretreated by plasma surface treatment technology to increase surface activity.

[0017] Preferably, the viscosity of the liquid adhesive ranges from 1000 cps to 10000 cps, and the liquid adhesive contains a nanoparticle additive.

[0018] Preferably, the mass ratio of the liquid adhesive to the inorganic fiber is 1:9 to 2:8.

[0019] Preferably, in step (c), mixing is performed by a high-speed disperser to ensure that the liquid adhesive is evenly distributed on the inorganic fibers, the mixing time is 5 minutes to 15 minutes, and the temperature is controlled at 20° C. to 40° C. during the mixing process.

[0020] Preferably, in step (d), the molding and pressurizing process is maintained at a temperature of 80° C. to 150° C. for 20 minutes to 60 minutes.

[0021] Preferably, in step (e), the curing treatment is performed by heat curing at a temperature of 80° C. to 120° C. for a duration of 30 minutes to 120 minutes.

[0022] Preferably, the inorganic fibers are modified in step (a) by a technique combining plasma surface treatment and photocatalyst coating, so as to enhance the bonding force between the fibers and the adhesive while imparting additional self-cleaning and antibacterial properties to the board.

[0023] Preferably, in step (a), the modification is carried out by combining plasma surface treatment with photocatalyst coating to simultaneously enhance the bonding force between the fiber and the adhesive and to impart additional antibacterial and self-cleaning properties to the board.

[0024] Preferably, the liquid adhesive is added with one or more nanoparticle reinforcing agents in step (b) to improve its fluidity and interaction with the inorganic fibers, and the nanoparticle reinforcing agents are selected from one or more of graphene, silica, and carbon nanotubes.

[0025] The present invention has at least the following beneficial effects:

[0026] (1) This scheme uses plasma surface treatment technology to modify the surface of inorganic fibers, significantly improving the interfacial bonding between the fibers and the adhesive, thereby improving the overall strength and stability of the board. In addition, by adding nanoparticle additives to the liquid adhesive, not only the bonding between the fibers and the adhesive is enhanced, but also the mechanical properties of the board, such as tensile strength, compressive strength and elastic modulus, are significantly improved.

[0027] (2) This solution simplifies the production process, improves production efficiency, and ensures uniform distribution and stability of the adhesive by using a high-speed disperser to efficiently mix inorganic fibers with liquid adhesive at an appropriate temperature. By applying appropriate pressure and temperature during the molding process, the board is ensured to have high density and high strength, and the temperature resistance and moisture resistance of the board are improved.

[0028] (3) This solution ensures that the adhesive is fully cured by rapid thermal curing, thereby improving the durability of the board. In addition, the surface coating treatment significantly enhances the scratch resistance and chemical resistance of the board, giving the board additional self-cleaning and antibacterial properties. Due to the high performance characteristics of the board, the inorganic fiberboard prepared by the present invention can be used in a wider range of fields, including but not limited to building exterior walls, interior wall decoration, partition systems, fireproof and soundproof materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0030] Figure 1 This is a diagram of the preparation method of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] See also Figure 1 The present invention provides a technical solution: a method for preparing an inorganic fiberboard using a liquid glue, comprising the following steps:

[0033] (a) Using plasma surface treatment technology to modify the surface of inorganic fibers to enhance the bonding force between the fibers and the adhesive;

[0034] (b) preparing a liquid adhesive comprising modified polyurethane or modified epoxy resin, wherein the liquid adhesive contains a nanoparticle additive for further enhancing the bonding force with the inorganic fiber;

[0035] (c) efficiently mixing the inorganic fiber with the liquid adhesive by a high-speed disperser at a temperature of 20° C. to 40° C. to ensure the stability and uniformity of the adhesive;

[0036] (d) forming the mixed material through a forming device, wherein the forming process includes pressurizing the material to a pressure range of 5 MPa to 20 MPa through a hydraulic press to ensure that the plate has high density and high strength;

[0037] (e) performing rapid thermal curing treatment on the formed sheet;

[0038] (f) Post-processing including precision cutting and fine grinding, and also surface coating treatment, wherein the coating contains nano-scale fillers and functionalized polymers to significantly enhance the scratch resistance and chemical resistance of the coating.

[0039] It should be noted that the method can produce an inorganic fiberboard with excellent physical properties by using a specific surface treatment technology and an efficient mixing process.

[0040] Step (a) Surface modification of inorganic fibers:

[0041] Raw material selection: select one or more of glass fiber, rock wool fiber, ceramic fiber, calcium silicate fiber as the inorganic fiber raw material.

[0042] Surface modification: Use plasma surface treatment technology to pre-treat the above inorganic fibers to increase the active points on the fiber surface to enhance the bonding force between the fiber and the adhesive used later. During the plasma treatment process, photocatalyst coating technology can be combined at the same time to give the board self-cleaning and antibacterial properties.

[0043] Step (b) Preparation of liquid adhesive:

[0044] Adhesive composition: A liquid adhesive containing modified polyurethane or modified epoxy resin is prepared, and the viscosity of the adhesive ranges from 1000cps to 10000cps.

[0045] Additives: Add nanoparticle additives (such as graphene, silica, carbon nanotubes) to the adhesive to further enhance the bonding between the adhesive and the inorganic fibers and improve the fluidity and heat resistance of the adhesive.

[0046] Step (c) Efficient Mixing:

[0047] Mixing conditions: Use a high-speed disperser to mix the inorganic fiber and the liquid adhesive for 5 to 15 minutes at a temperature of 20°C to 40°C to ensure that the adhesive is evenly distributed on the fiber surface and maintain the stability of the adhesive.

[0048] Step (d) molding and pressurization:

[0049] Molding: The mixed material is fed into the molding equipment and pressurized to a pressure range of 5MPa to 20MPa at a temperature of 80℃ to 150℃ by a hydraulic press for 20 minutes to 60 minutes to ensure that the sheet has high density and high strength.

[0050] Step (e) rapid thermal curing:

[0051] Curing conditions: Heat curing treatment is carried out at a temperature of 80℃ to 120℃ for 30 minutes to 120 minutes to ensure that the adhesive is fully cured and improve the stability and durability of the board.

[0052] Step (f) post-processing:

[0053] Cutting and grinding: The formed plates are precisely cut and finely ground to achieve the required size and surface quality.

[0054] Surface coating: Surface coating treatment containing nano-scale fillers and functionalized polymers to significantly enhance the coating's scratch and chemical resistance.

[0055] Furthermore, the inorganic fiber is preferably a mixture of glass fiber and ceramic fiber. The mass ratio of the liquid adhesive to the inorganic fiber is 1.5:8.5. The nanoparticle additive is a mixture of graphene and silicon dioxide.

[0056] In some embodiments, the inorganic fiber is selected from one or more of glass fiber, rock wool fiber, ceramic fiber, and calcium silicate fiber, and the inorganic fiber is pre-treated by plasma surface treatment technology to increase surface activity.

[0057] The viscosity of the liquid adhesive ranges from 1000 cps to 10000 cps, and the liquid adhesive contains a nanoparticle additive, wherein the additive is used for enhancing the bonding force between the liquid adhesive and the inorganic fiber.

[0058] The mass ratio of the liquid adhesive to the inorganic fiber is 1:9 to 2:8, preferably 1.5:8.5, and the ratio can ensure the best combination of fiber and adhesive to obtain the best board performance.

[0059] In step (c), mixing is performed by a high-speed disperser to ensure that the liquid adhesive is evenly distributed on the inorganic fibers. The mixing time is 5 to 15 minutes, and the temperature is controlled at 20° C. to 40° C. during the mixing process to ensure the stability of the adhesive.

[0060] In step (d), the molding and pressurizing process is maintained at a temperature of 80° C. to 150° C. for 20 minutes to 60 minutes to ensure high density and high strength of the board.

[0061] In step (e), the curing treatment is performed by heat curing at a temperature of 80° C. to 120° C. for a duration of 30 minutes to 120 minutes, so as to completely cure the adhesive and improve the stability and durability of the board.

[0062] The inorganic fibers are modified in step (a) by a technology combining plasma surface treatment and photocatalyst coating, which is used to enhance the bonding force between the fibers and the adhesive while giving the board additional self-cleaning and antibacterial properties.

[0063] In step (a), the surface is modified by combining plasma surface treatment with photocatalyst coating to simultaneously enhance the bonding force between the fiber and the adhesive and to impart additional antibacterial and self-cleaning properties to the board.

[0064] The liquid adhesive is added with one or more nanoparticle reinforcing agents in step (b) to improve its fluidity and interaction with the inorganic fibers. The nanoparticle reinforcing agents are selected from one or more of graphene, silicon dioxide, and carbon nanotubes to significantly improve the mechanical properties and heat resistance of the board.

[0065] The detailed preparation process of the present invention is as follows:

[0066] By using plasma surface treatment technology, new functional groups can be introduced on the surface of inorganic fibers, increasing the polarity and roughness of the fiber surface, thereby improving the interfacial bonding between the fiber and the adhesive. In addition, plasma treatment can also remove pollutants on the fiber surface and improve its cleanliness. Photocatalyst coating technology forms a layer of photocatalyst material (such as titanium dioxide TiO2) on the fiber surface, generating free radicals under light conditions. These free radicals can decompose organic pollutants adsorbed on the surface of the board, giving the board self-cleaning and antibacterial functions. The modified polyurethane or epoxy resin has better fluidity, lower shrinkage and higher temperature resistance, can better adapt to the characteristics of inorganic fibers, and improve the overall performance of the board. Nanoparticles (such as graphene, silica, carbon nanotubes) as additives can fill the gap between the fiber and the adhesive, reduce the porosity, and improve the density of the board; at the same time, the high surface energy of the nanoparticles can also enhance the bonding force between the adhesive and the fiber, thereby improving the mechanical properties of the board. The high-speed disperser can fully mix the fiber and the adhesive at a relatively low temperature (20°C to 40°C), ensuring that the adhesive is evenly covered on the fiber surface, while avoiding premature curing of the adhesive or damage to the fiber structure due to excessive temperature. Appropriate mixing time and temperature can ensure the uniform distribution of the adhesive on the fiber, while maintaining the stability of the adhesive and avoiding premature curing or volatilization. Pressurizing the mixed material at a certain temperature (80°C to 150°C) and pressure (5MPa to 20MPa) by a hydraulic press can promote close bonding between the fibers and between the fibers and the adhesive, thereby improving the density and strength of the sheet. The temperature and pressure conditions during the molding process can accelerate the curing reaction of the adhesive and enable the sheet to quickly form a stable structure. Heat curing treatment at a higher temperature (80°C to 120°C) can accelerate the curing process of the adhesive and ensure that the adhesive is fully cured, thereby improving the stability and durability of the sheet. Finally, the dimensional accuracy and surface quality of the sheet can be adjusted through precise cutting and fine grinding to meet the needs of different application scenarios. Furthermore, the surface coating contains nano-scale fillers and functionalized polymers, which can further enhance the hardness and wear resistance of the board surface, improve its scratch resistance and chemical resistance, and extend the service life of the board.

[0067] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Preparation method of inorganic fiberboard made of liquid glue, Features: The following steps are involved: (a) Using plasma surface treatment technology to modify the surface of inorganic fibers to enhance the bonding force between fibers and adhesives; (b) preparing a liquid adhesive comprising modified polyurethane or modified epoxy resin, wherein the liquid adhesive contains a nanoparticle additive for further enhancing the bonding force with the inorganic fiber; (c) efficiently mixing the inorganic fiber with the liquid adhesive by a high-speed disperser at a temperature of 20° C. to 40° C.; (d) forming the mixed material through a forming device, wherein the forming process includes pressurizing the mixed material to a pressure in the range of 5 MPa to 20 MPa through a hydraulic press; (e) performing rapid thermal curing treatment on the formed sheet; (f) performing post-processing, including precision cutting and fine grinding, and also including surface coating treatment, wherein the coating contains nano-scale fillers and functionalized polymers.

2. The method for preparing inorganic fiberboard by liquid glue according to claim 1, Features: The inorganic fiber is selected from one or more of glass fiber, rock wool fiber, ceramic fiber, and calcium silicate fiber, and the inorganic fiber is pre-treated by plasma surface treatment technology to increase surface activity.

3. The method for preparing inorganic fiberboard by liquid glue according to claim 2, Features: The viscosity of the liquid adhesive ranges from 1000 cps to 10000 cps, and the liquid adhesive contains a nanoparticle additive.

4. The method for preparing inorganic fiberboard by using liquid glue according to claim 3, Features: The mass ratio of the liquid adhesive to the inorganic fiber is 1:9 to 2:

8.

5. The method for preparing inorganic fiberboard by liquid glue according to claim 1, Features: In step (c), mixing is performed by a high-speed disperser to ensure that the liquid adhesive is evenly distributed on the inorganic fibers. The mixing time is 5 to 15 minutes, and the temperature is controlled at 20° C. to 40° C. during the mixing process.

6. The method for preparing inorganic fiberboard by using liquid glue according to claim 1, Features: In step (d), the molding and pressurizing process is maintained at a temperature of 80° C. to 150° C. for 20 minutes to 60 minutes.

7. The method for preparing inorganic fiberboard by using liquid glue according to claim 5, Features: In step (e), the curing treatment is performed by heat curing at a temperature of 80° C. to 120° C. for a duration of 30 minutes to 120 minutes.

8. The method for preparing inorganic fiberboard by using liquid glue according to claim 7, Features: The inorganic fibers are modified in step (a) by a technology combining plasma surface treatment and photocatalyst coating, which is used to enhance the bonding force between the fibers and the adhesive while giving the board additional self-cleaning and antibacterial properties.

9. The method for preparing inorganic fiberboard by liquid glue according to claim 1, Features: In step (a), the surface is modified by combining plasma surface treatment with photocatalyst coating to simultaneously enhance the bonding force between the fiber and the adhesive and to impart additional antibacterial and self-cleaning properties to the board.

10. The method for preparing inorganic fiberboard by using liquid glue according to claim 9, Features: The liquid adhesive is added with one or more nanoparticle reinforcing agents in step (b) to improve its fluidity and interaction with the inorganic fibers. The nanoparticle reinforcing agents are selected from one or more of graphene, silicon dioxide, and carbon nanotubes.